Obesity and overweight among the poor and marginalized in rural Mexico: impact analysis of the effect of school breakfasts on children aged five to eleven - Odra A. Saucedo-Delgado; Marcela De-La-Sota-Riva-Echánove; Leovardo Mata (Revista Iberoamericana de Estudios de Desarrollo)
This article estimates the effect of the School Breakfast Program (SBP) on overweight and obese Mexican children aged five to eleven living in a poor and marginalized rural context during 2012-2019. Using data from the 2012, 2016, 2018, and 2019 National Health and Nutrition Surveys (ENSANUT), as well as propensity score matching techniques, this research compares the usual food intake of a group of children enrolled on the SBP with a control group that were not. The results indicate that SBP recipients include more overweight children, and that these consume unhealthy foods, including sugary drinks, snacks, sweets, and desserts, more frequently than those in the control group. There was no significant difference in the children’s obesity between the two groups. These findings highlight the need for a more comprehensive school breakfast program, that is connected to the food and nutritional security approach and is designed and implemented according to each Mexican region’s specific alimentary requirements and socioeconomic needs.